Effect of temperature and relative humidity on the germination of Bremia lactucae Regel sporangia - Yáñez López Ricardo; Quijano Carranza Juan Ángel; Bucio Villalobos, Carlos Manuel; Hernández Zul María Irene; Arreguín Centeno José Honorato; Narro Sánchez Jesús (Revista Mexicana de Ciencias Agrícolas, 2018)
The purpose of this work, performed in 2009, was to study the effect of temperature and relative humidity on the germination of Bremia lactucae Regel sporangia. The effect of these variables on the in vitro germination of sporangia was evaluated in incubation chambers, with 21 treatments formed by the temperature levels of 5, 10, 15, 20, 25, 30, 35 oC combined with humidities of 70, 80, 90%. Germination was evaluated 24 h after the treatment was established. A statistical analysis was carried out to determine the importance of these variables and their interaction on the germination of sporangia and infer on the optimum temperature and humidity ranges. We found that there is a significant effect of the interaction between these variables on germination, which appears starting at 5 oC until 25 oC. The treatment that presented the highest percentage of germination was 10 oC, in combination with a relative humidity of 90%. Based on an surface response analysis, we concluded that the optimum of sporangia germination can be obtained with with temperatures ranging from 9.5 to 12.5 oC with a relative humidity of 90%.